ESTIMASI VALUE AT RISK PORTOFOLIO VALUTA ASING PADA KONDISI PANDEMI COVID-19 MENGGUNAKAN COPULA - ANJAR ANGGRAINI; KOMANG DHARMAWAN; I WAYAN SUMARJAYA (Mathematics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2025)
The Coronavirus disease (Covid-19) has been officially declared a pandemic by the World Health Organization (WHO). This pandemic affects not only the health of the population but also weakens the rupiah exchange rate. Fluctuations in exchange rate changes can affect the investment value, so investors need to take risk measurements. This study discusses the measurement of portfolio loss risk which is composed of a combination of USD, JPY, GBP, and EUR currency exchange rates using the value at risk (VaR) risk measure. Dependent structure analysis was carried out using the Gumbel, Clayton, and Frank copulas approach from the Archimedean copula family. The results obtained from this study are based on portfolio calculations composed of USD-GBP, JPY-GBP, and EUR-USD currency exchange rates at , , and confidence levels in the next one-day period. The highest VaR of is achieved by the EUR-USD portfolio at a confidence level using the Gumbel copula. Meanwhile, the lowest estimated VaR of is achieved by the EUR-USD portfolio at a confidence level using the Gumbel copula.